1994
DOI: 10.2134/jeq1994.00472425002300010013x
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of Sorption Coefficients for Fungicides in Soil and Turfgrass Thatch

Abstract: Environmental fates of turf‐applied fungicides are not well understood. The role of thatch as a sorptive surface for fungicides has not been evaluated. Thatch may decrease mobility of fungicides and decrease their potential to be transported off‐site. Batch type sorption studies were conducted to determine sorption coefficients (Kf) for the fungicides triadimefon, [1‐(4‐chlorophenoxy)‐3,3‐dimethyl 1‐1‐(1H‐1,2,4‐triazol‐1‐g‐1) butanone], vinclozolin [3‐(3,5‐dichlorophenyl)‐5‐methyl‐5‐vinyl‐1,3‐oxazolidine‐2,4‐d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
32
0

Year Published

1999
1999
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(37 citation statements)
references
References 0 publications
5
32
0
Order By: Relevance
“…Therefore, the pesticides were primarily on the leaf tissues rather than in the underlying thatch or soil at the onset of precipitation. Others have shown that pesticide residues can be found in thatch where they may be sorbed [34][35][36], resulting in reduced mobility to underlying soil [37,38]. It is important to point out that numerous environmental and management factors contribute to the availability of pesticides for movement with overland flow.…”
Section: Chemographs and Partition Coefficientsmentioning
confidence: 99%
“…Therefore, the pesticides were primarily on the leaf tissues rather than in the underlying thatch or soil at the onset of precipitation. Others have shown that pesticide residues can be found in thatch where they may be sorbed [34][35][36], resulting in reduced mobility to underlying soil [37,38]. It is important to point out that numerous environmental and management factors contribute to the availability of pesticides for movement with overland flow.…”
Section: Chemographs and Partition Coefficientsmentioning
confidence: 99%
“…Other studies have shown greater pesticide adsorption capacities on thatch or dry straw than on soil for fungicides (Dell et al 1994) and herbicides (Reddy et al 1995;Rautri et al 1997). High organic matter soils have much higher atrazine and metolachlor K d values (i.e., 40 and 66 L kg 21 , respectively) than low organic matter mineral soils Seybold and Mersie 1996).…”
Section: Resultsmentioning
confidence: 94%
“…The presence of turfgrass cover drastically reduced the movement of fungicide residues into the soil. Dell et al (1994) conducted sorption studies for triadimefon, vinclozolin, and chloroneb in thatch and soil. They were able to show that thatch drastically increased the sorption of fungicides.…”
Section: Fungicide Mobilitymentioning
confidence: 99%
“…Horst et al (1996) monitored the vertical movement and dissipation of pendimethalin, chlorpyrifos, isazofos, and metalaxyl. Sorption studies were conducted for the fungicides triadimefon, vinclozolin, and chloroneb in thatch and soil (Dell et al, 1994). Frederick et al (1994) observed the degradation of chloroneb, triadimefon, and vinclozolin in soil, thatch, and grass clippings under laboratory conditions.…”
Section: Root Diseasesmentioning
confidence: 99%